Structured Long Interview and Clinical Examination (SLICE) as Formative Assessment Tool in Clinical Clerkship: Medical Students Perspective - Wajiha Shadab; Amna Ahmed Noor; Saira Waqqar; Gul Muhammad Shaikh (Journal of the Pakistan Medical Association, 2021)
Objective: This study aimed to assess the medical students’ opinions and views on undertaking SLICE as a formative assessment. Methods: This was a qualitative, exploratory study. Purposive sampling technique was used to select final year medical students who have undertaken a formative assessment through SLICE in their clerkship rotation. Total 32 students participated in this study .Four sets of focus group discussions (FGD) were conducted from medical students who had recently gone through their clinical clerkship modules for Pediatrics, General Medicine, General Surgery and Gynecology& Obstetrics. Each recorded FGD was transcribed verbatim. Thematic analysis was conducted manually. Themes were identified from the transcribed data, coded and analyzed. In order to achieve adequate coding and researcher reliability, investigator triangulation was performed. The initial thematic analysis was performed by the primary investigator. Thereafter, two more investigators independently analyzed the data. Before the data was finalized, all the three investigators reached a final consensus upon the themes that had emerged, ensuring triangulation of the analyzed data. Results: A four staged thematic analysis was conducted, in which five major themes and five sub-themes emerged. The main themes being: Purpose, Learning, Timing, Relevancy and Fairness of SLICE. Conclusion: The students generally thought that SLICE was effective in enhancing their clinical skills learning and should be conducted more frequently with minor adjustments. Continuous...